2015
DOI: 10.1080/21693277.2015.1013582
|View full text |Cite
|
Sign up to set email alerts
|

Developing location indicators for Agricultural Service Center: a Delphi–TOPSIS–FAHP approach

Abstract: The main goal of this paper is to construct objectives and attributes of the service centers location problem. This problem is often found within production management as a location problem, when designing for example supply chains or manufacturing layouts. The main contribution of this paper is constructing related location indicators. Since there was no similar literature in this discipline, so a Delphi survey applied to quantify expert's attitudes about location problem of Agricultural Service Center (ASC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…They examined the problem of logistics and distribution of fresh products. Zangeneh et al [21] used an analytical hierarchical process (AHP) for the identification of factors affecting the distribution of cold-chain products. The study suggested to include cost, speed, and service of delivery in the analysis of relevant problems.…”
Section: Distribution Design Of Cold-chain Productsmentioning
confidence: 99%
“…They examined the problem of logistics and distribution of fresh products. Zangeneh et al [21] used an analytical hierarchical process (AHP) for the identification of factors affecting the distribution of cold-chain products. The study suggested to include cost, speed, and service of delivery in the analysis of relevant problems.…”
Section: Distribution Design Of Cold-chain Productsmentioning
confidence: 99%
“…Barzekar et al (2011) used this method to investigate the criteria and indicators for sustainable ecotourism. Zangeneh et al (2015) considered identifying the agricultural service center location and used the method to construct the location objectives and attributes. Hanna and Noble (2015) determined effective criteria for environmental management and protection based on the input of expert researchers from Canada and the European Union using this method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The location of perishable food distribution centers was studied by Zvi Drezner [ 11 ], who suggested that the location of the distribution center would affect the inventory costs and location costs, so the two costs were considered in the total cost calculation. Morteza Zangeneh [ 12 ] proposed that service, cost, and speed were important factors influencing the distribution of fresh agricultural products, then the indicators that affect the location of agricultural service centers were identified, and the weights of these factors were calculated by fuzzy analytic hierarchy process.…”
Section: Literature Reviewmentioning
confidence: 99%